Oral health‐related quality of life of older people from three South American cities. (19th March 2012) - Fuentes‐García, Alejandra; Lera, Lydia; Sánchez, Hugo; Albala, Cecilia
<x xml:space="preserve">Abstract</x> Objective: To describe subjective oral health status and its association with overall health conditions and socioeconomic factors in the elderly (60 years and older) living in the capital cities with the oldest average populations in South America. Background: Oral diseases are a public health problem, frequently neglected in older adults. In recent years, the subjective assessment of psychological and social consequences of the problems related to oral health has been valued. One of the instruments used to estimate the Oral Health‐Quality of Life is the Geriatric Oral Health Assessment (GOHAI). Material and methods: Representative samples from SABE study (1999–2000) of Santiago (n = 1301), Buenos Aires (n = 1043), and Montevideo (n = 1450) aged 60 and over community‐dwelling people. We assessed OH‐QoL (GOHAI), self‐reported missing teeth, denture use, and self‐rated‐health, among other indicators. Logistic regression models(GOHAI < 58) for each city, adjusted by sex and age, were applied. Results: GOHAI average scores were higher in Montevideo (54.8 ± 6.1) than in Buenos Aires (53.1 ± 7.4) and Santiago (49.9 ± 8.6). A pronounced gradient of the oral condition and GOHAI scores were observed within the three‐cities. Denture use ‐less prevalent in Santiago and more common among women‐ is a protective factor against a poor OH‐QoL. Conclusion: Socioeconomic inequalities in oral health status and OH‐QoL are observed in the three cities. The increasing life expectancy emphasizes the need to integrate prevention and treatment efforts, as a way to improve OH‐QoL over the course of a lifetime.